Corporate Governance Mechanisms and Dividend Payouts of Listed Non-Financial Firms: Evidence from Selected Sub-Saharan African Countries - Omoruyi Aigbovo; Ikavbo Esther Evbayiro-Osagie (Faculty of Economics, Universitas Sriwijaya, 2022)
This study examined the effects of corporate governance elements on the dividend distribution of listed corporations in the three Sub-Saharan African countries of South Africa, Nigeria, and Kenya. The inquiry used inferential statistics in the form of the system generalized method of moments (GMM). The findings show that corporate governance factors have a fundamental influence on dividend distribution in the three Sub-Saharan African countries. More specifically, board independence has a significant negative influence on dividend payout, but board size, board gender diversity, and management ownership all directly and materially affect the dividend payout of listed non-financial firms. The paper suggested that authorities in charge of regulation in the examined Sub-Sahara Africa nation’s securities exchange have to continually ensure that all firms comply stringently with the codes of corporate governance in other to limit market infractions and boost stakeholders’ confidence and thus stimulate more investment in their respective capital markets.